Multi Hop Transmission in IEEE 802.11 Low Rate Ad Hoc Network Using ARP-Route - Md Isa, Ida Syafiza; Syed Ariffin, Dr Sharifah Hafizah; Abdul Latif, Prof Norsheila; Mohd Shaari Azyze, Nur Latif Azyze; Tuani Ibrahim, Ahamed Fayeez (Penerbit Universiti, UTeM, 2013)
Ad hoc networks are becoming more important in the modern complex environment. The ad hoc network can be used to instantly connect to the local or remote networks such as the Internet without the need of pre-existing infrastructure or centralized administration. The users of the network together will establish the infrastructure. The disadvantage of wireless communication is that it has limited range of radio transmission. Due to this, multiple network ‘hops’ are needed for one device to exchange data with another device across the network. In an ad hoc network, these devices will not only operate as a host but also as a router to forward the packets. There are varieties of routing protocols targeted for this environment that have been proposed and developed. However, most of them suffer from high overhead data traffic. The main purpose of this project is to implement the ad hoc network with the existing network protocol that had already been used in network environment which is the Address Resolution Protocol (ARP). ARP was designed to announce or find MAC addresses. The novelty of this study is that we have extended the usage of the ARP protocol to act as routing protocol in wireless ad hoc network. The ARP route provides two new operation types, ARP Forward Request and ARP Forward Reply to allow the multihop transmission using intermediate nodes to forward the request and reply. These two operation types only used the current operation codes which are ‘0x0001’ for request and ‘0x0002’ for reply. This work on the routing protocol creates a new operation code for the ARP forwarding scheme which is ‘0x000c’ for forwarding. We have successfully managed to create a multi hop transmission in an ad hoc network by using the current existing operation code for the ARP forwarding. The work scope focus only on proving that the method can be applied hence it is not necessarily to prove the effectiveness of this proposed method yet. Therefore, the outcome of the study shows that the data can be sent through multi hop transmission until it reaches the destination. The 802.11b test-bed has been configured and the ARP routing protocol has been implemented for multi hop transmission. The experiment in the open space provides the comparison of environment with obstacles and without obstacles. We manage to get more than 50% of packet receive at a place with no obstacles and more than 45% in a place with obstacles. The proof of method is shown by using several graphs namely in terms of time, packet loss and also throughput.